Water exchange on beryllium complexes: Part VIII - Influence of neutral electron pair donors - Walther, Markus; Budimir, Ana; Puchta, Ralph (Journal of Coordination Chemistry, 2012)
In this article, water exchange reactions on [Be(L)(H2O) 3]2+ (L=NH3-x(CH3)x, PH3-x(CH3)x, AsH3-x(CH 3)x, OH2-x(CH3)x, SH 2-x(CH3)x, SeH2-x(CH 3)x, pyridine, 4-fluoropyridine, 4-bromopyridine, 4-chloropyridine, 4-hydroxypyridine, 4-thiolopyridine, 4-selenidopyridine, 4-nitrilopyridine, 1,4-diazine, 1,3,5-triazine, HCN, acetonitrile, and benzonitrile) are examined, utilizing the B3LYP//6-311+G** density functional for geometry optimizations, and B3LYP//6-311+G** both with and without the CPCM solvent model as well as MP2(full)//6- 311+G** for subsequent single-point energy calculations. In all examined cases, the results prove that these complexes show associative interchange mechanisms for water exchange. With the exception of the NH x(CH3)3-x series of ligands, activation energy barriers vary little, making these ligands mostly spectator ligands. Geometrical parameters vary mainly with the ligand size. © 2012 Taylor & Francis.
CRIS-Team Scopus Importer:2026-01-22
Keywords: Beryllium; Ligand effects; Quantum-chemical calculations; Solvent exchange